Motivation of UP Mindanao student leaders - Beluan, Yuri M.
Leadership is a task of influencing group members in achieving group goals. In UP Mindanao where there are eighteen (18) recognized student organizations, student leaders wanted to become leaders of their organizations because of several reasons which motivates them. From the survey that was conducted, one of the motivations of UP Mindanao student leaders is the motive to serve, as an obligation being subsidized by the Filipino people. Along with other motivations, UP Mindanao student leaders wanted to become leaders of their organizations because they wanted to serve.